Timing error by children identified with dcd leads to inefficient jump performance - Williams, M.; Maschette, W.; Lythgo, N. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to identify outcome and response differences in vertical jumping between children typically developing (TD) and those identified with Developmental Coordination Disorder (DCD). Efficient vertical jumping is essential to physical activity in children. The TD group jumped higher as a result of a faster vertical velocity of the centre of mass (VCOM) at take-off. Peak VCOM was greater and occurred closer to take-off in TD when compared to DCD. Earlier occurrence of peak VCOM observed in DCD caused a noticeable loss of VCOM at take-off compared to TD. The timing of the peak VCOM before take-off resulted in large group variation for DCD (CV = 50%) compared to the stereotyped TD (CV = 6%). The difference between groups emphasises coordination difficulties of DCD during vertical jumping.